An Internal Performance Assessment of CancerGene Connect: An Electronic Tool to Streamline, Measure and Improve the Genetic Counseling Process. Issue 6 (12th June 2014) - Pritzlaff, Mary; Yorczyk, Arielle; Robinson, Linda S.; Pirzadeh‐Miller, Sara; Lin, Tirun; Euhus, David; Ross, Theodora S
Abstract: CancerGene Connect ( CGC ) is a web‐based program that combines the collection of family and medical history, cancer risk assessment, psychosocial assessment, report templates, a result tracking system, and a patient follow up system. The performance of CGC was assessed in several ways: pre‐appointment completion data analyzed for demographic and health variables; a time study to assess overall time per case and to compare the data entry by the genetic counselor compared to the patient, and a measured quality assessment of the program via observation and interview of patients. Prior to their appointment, 52.3 % of 2, 414 patients completed the online patient questionnaire section of CGC . There were significant differences in completion rates among racial and ethnic groups. County hospital patients were less likely to complete the questionnaire than insured patients ( p < 0.0001); and likewise uninsured patients and patients with Medicare/Medicaid were less likely to complete the questionnaire than private patients ( p < 0.0001). The average genetic counseling time per case was 82 min, with no significant differences whether the counselor or the patient completed CGC. CGC reduces genetic counselor time by approximately 14–46 % compared to average time per case using traditional risk assessment and documentation methods previously reported. All surveyed users felt the questionnaire was easy to understand. CGC is an effective tool that streamlines workflow, and provides a standardized data collection tool that can be used to evaluate and improve the genetic counseling process.